Implementation of Fuzzy Logic on the Feasibility of Duck Egg Quality - Dhiya Rizqi Bagus Wibowo; Edmund Banyu Kauripan; Khairunnissa Zahran Ansyafa; Nabil Arif A'isy; Muhamad Fadhil; Inna Novianty; Nanda Octavia; Ivan De NeroI (Journal of Applied Science, Technology & Humanities | JASTH, 2024)
Eggs are a staple food, with chicken eggs being the most common choice. However, duck eggs are gaining popularity due to their nutritional value. Ducks, a local poultry breed, are seeing increased interest, leading to a growth in the national duck population. Duck eggs themselves are one source of animal protein that is rich in nutrients and easily digested. Duck eggs have a very high protein content, which is 13.1 grams per 100 grams. The purpose of building a decision support system for duck egg selection is to help people choose quality duck eggs for consumption. Data collection techniques in this study use literature studies and include direct calculations and using MATLAB software to develop a Fuzzy logic system in determining the feasibility of duck egg quality. The results showed that in the example case for a duck egg that weighs 5.5 grams and then the thickness of the shell is 7.5 mm and the viscosity of the egg contents is given a number of 7, then the egg is still said to be suitable for consumption. This contributes to improving food quality in Indonesia by classifying the feasibility of eggs for public consumption.